Student's Critical Thinking Ability in Algebra Material using Process Oriented Guided Inquiry Learning (POGIL) - Nia Kurniati; Dwi Ivayana Sari; Enny Listiawati (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The purpose of this study was to describe the ability of teachers to manage to learn using the POGIL model and to describe students' critical thinking skills after being taught using the POGIL model. This type of research was quantitative research. The research design used was one group posttest only, with a population of all VII grade students of SMP N 1 Geger, and one class was taken randomly as a sample, namely class VIIC as the sample. The data collection techniques used were observation and tests. Observations were made to obtain data on the ability of teachers in managing to learn using the POGIL learning model and tests were carried out to obtain data on students' critical thinking abilities. The data analysis used was descriptive statistical analysis. The results showed that the teacher's ability to manage to learn was said to be effective because the average results of the observed aspects in learning I and II were in good and very good categories. This shows that the teacher has carried out the learning process well and was by the steps of the POGIL learning model. The POGIL learning model was also able to develop students' critical thinking skills because the total percentage of students with high and moderate critical thinking skills was more than 80%. Keywords: critical thinking, POGIL learning model.